A Study Of Shock Absorption Performance Of Tapioca Starch As Cushioning Material For Packaging - Ibrahim, Maziah (IRC, 2016)
Packaging material was an important product that was used to all of the people in the world. The demand of this product was quite high due to the usage of packaging material by the people and the lower cost of the production. Due to the lack of information regarding formulation and fabrication of the starch polymer foam, this research was executed. Tapioca starch, ethylene vinyl-alcohol (EVA), stearic acid, distilled water and corn syrup were used to develop the tapioca starch polymer foam. The variables manipulation was the amount of water to produce the best starch polymer foam. A weight drop destructive test was conducted to find the optimum impact capability of the foam. The foam was placed on the top of the mirror and a weight of 0.05 kg was drop on to the foam with increasing the height until the mirror break. From the test, it can be found that the shock absorption ability of tapioca starch polymer with the thickness of 0.4 cm was higher than polyurethane and polystyrene because it can withstand higher impact force to protect the mirror form break. Furthermore, the shock absorption of the tapioca starch polymer foam with the thickness of 0.8 cm gave the result of impact force (638 N/m) which was higher than polyurethane (481 N/m).